Program Kampung Keluarga Berencana Menurut Hukum Islam - Musyafaah, Nur Lailatul (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2018)
The KB village has several programs, namely Family Planning (KB), Tribina which includes Family Development Coaching, Adolescent Family Development, Elderly Family Development (BKB, BKR, and BKL), Efforts to Increase Prosperous Family Income (UPPKS), and Information and Counseling Center Youth (PIK_RM). Based on the analysis of Islamic law, the Family Planning Village program in general is in accordance with the principles of Islamic law, but there are a number of programs whose laws are disputed by Jurisprudence. The Tribina program is in accordance with Islamic law, because the obligation of parents to care for and educate their children from toddlers to adolescents is good, and caring for elderly parents is an obligation of children to their parents. Regarding the family planning program, the majority of scholars allow for the use of contraceptives not to be permanent, not harmful and carried out by experts, while the permanent contraception, such as vasectomy and tubectomy, the majority of scholars forbid them. In connection with the UUPKS, the legal UUPKS may even be recommended because part of mutual assistance. But what needs to be considered is that the business must be in accordance with the concept of Islamic business, including not containing elements of gharar (uncertainty) and usury. The PIK_RM is in accordance with Islamic law, because fostering teenagers with proper and good guidance is highly recommended in Islamic law, so that they can become a superior generation and not fall into bad things. [Kampung KB memiliki beberapa program, yaitu Keluarga Berencana (KB), Tribina yang meliputi Bina Keluarga Balita, Bina Keluarga Remaja, Bina Keluarga Lansia (BKB, BKR, dan BKL), Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPPKS), dan Pusat Informasi dan Konseling Remaja (PIK_RM). Berdasarkan analisis hukum Islam, program Kampung KB secara umum telah sesuai dengan prinsip hukum Islam, namun ada beberapa program yang hukumnya diperselisihkan oleh fukaha. Program Tribina telah sesuai dengan hukum Islam, karena kewajiban orang tua merawat dan mendidik anaknya dari balita hingga remaja dengan baik, dan merawat orang tua yang sudah lansia merupakan kewajiban anak kepada orang tuanya. Mengenai program KB, mayoritas ulama membolehkan selama penggunaan alat kontrasepsi tersebut tidak bersifat permanen, tidak membahayakan, dan dilakukan oleh orang yang ahli, sedangkan alat kontrasepsi yang permanen, seperti vasektomi dan tubektomi, mayoritas ulama mengharamkannya. Berkaitan dengan UUPKS, UUPKS hukumnya boleh bahkan dianjurkan karena bagian dari saling tolong menolong, namun yang perlu diperhatikan adalah usaha tersebut harus sesuai dengan konsep bisnis Islam, diantaranya tidak mengandung unsur gharar dan riba. Adapun PIK_RM, sesuai dengan hukum Islam, karena membina remaja dengan pembinaan yang benar dan baik sangat dianjurkan dalam hukum Islam, agar mereka bisa menjadi generasi yang unggul dan tidak terjerumus kepada hal-hal yang buruk.]